Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Give the Laurent series development of the function $f(z)=\frac{1}{z(z-1)(z-2)}$ in the three rings $A_1=\{z:|z|<1\}$, $A_2=\{z:1<|z|<2\}$ and $A_3=\{z:2<|z|\}$.

I have gotten the partial fraction form $f(z)=\frac{1}{2z}-\frac{1}{z-1}+\frac{1}{z-2}$

For $A_1$, I think it's the standard Taylor expansion about 0 and I can do this for the second and third terms:

$-\frac{1}{z-1}=(1-z)^{-1}=\sum^\infty_{n=0}z^n$ and $\frac{1}{2(z-2)}=\frac{1}{4}\sum^\infty_{n=0}(\frac{z}{2})^n$. How do I get the Taylor expansion of the first term?

I foresee similar problems if I work out the expansion for $A_2$ and $A_3$ as well, so a general method is appreciated. Thanks!

share|improve this question
add comment

2 Answers

up vote 2 down vote accepted

First of all, the partial fraction decomposition is $$ f(z) = \frac{1}{2z} - \frac{1}{z - 1} + \frac{1}{2(z - 2)}. $$ The Laurent series converges on an annulus, so $A_1$ must not contain the origin: $$ A_1 = \left\{z : 0 < |z| < 1 \right\}. $$ Then, you can just use the usual Taylor expansion around $z = 0$: $$ \begin{align} f(z) &= \frac{1}{2z} + \frac{1}{1 - z} - \frac{1}{4(1 - \tfrac{z}{2})} \\ &= \tfrac{1}{2}z^{-1} + \sum_{n=0}^\infty z^n - \tfrac{1}{4} \sum_{n=0}^\infty \left(\frac{z}{2}\right)^n \\ &= \tfrac{1}{2}z^{-1} + \sum_{n=0}^\infty \left(1 - \frac{1}{2^{n+2}}\right)z^n \\ &= \sum_{n=-1}^\infty \left(1 - \frac{1}{2^{n+2}}\right)z^n \\ &= \tfrac{1}{2}z^{-1} + \tfrac{3}{4} + \tfrac{7}{8}z + \tfrac{15}{16}z^2 + \cdots \end{align} $$

There is actually an easier way to expand the series (around $z = 0$) which generalizes nicely for the other regions: $$ f(z) = \frac{1}{z} \cdot \frac{1}{(z - 1)(z - 2)} = \frac{1}{z} \cdot \left( \frac{1}{1 - z} - \frac{1}{2 - z} \right). $$ Each of these is a geometric series that can be expanded inside or outside its radius of convergence. $$ \frac{1}{1 - z} = \begin{cases} \phantom{-}\sum_{n = 0}^\infty z^n, &|z| < 1, \\ -\sum_{n = 1}^\infty \frac{1}{z^n}, &|z| > 1. \end{cases} $$ Similarly, $$ \frac{1}{2 - z} = \frac{1}{2(1 - \tfrac{z}{2})} = \begin{cases} \phantom{-}\frac{1}{2}\sum_{n = 0}^\infty \left(\frac{z}{2}\right)^n = \frac{1}{2}\sum_{n = 0}^\infty \frac{z^n}{2^n} = \sum_{n = 0}^\infty \frac{z^n}{2^{n + 1}}, &|z| < 2, \\ -\frac{1}{2}\sum_{n = 1}^\infty \frac{1}{\left(\frac{z}{2}\right)^n} = -\frac{1}{2}\sum_{n = 1}^\infty \frac{2^n}{z^n} = -\sum_{n = 1}^\infty \frac{2^{n - 1}}{z^n}, &|z| > 2. \end{cases} $$ Now, for each of the three regions, choose the appropriate expansion, and combine them. For instance, on $A_2$, where $1 < |z| < 2$, $$ \begin{align} f(z) &= \frac{1}{z} \left(-\sum_{n = 1}^\infty \frac{1}{z^n} - \sum_{n = 0}^\infty \frac{z^n}{2^{n + 1}} \right) \\ &= -\sum_{n = 1}^\infty \frac{1}{z^{n + 1}} - \sum_{n = 0}^\infty \frac{z^{n - 1}}{2^{n + 1}}. \end{align} $$

share|improve this answer
add comment

For $\,A_1\,$:

$$|z|<1\implies\frac{|z|}2<1\implies$$

$$\frac1{2z}+\frac1{1-z}-\frac12\frac1{1-\frac z2}=\frac1{2z}+\left(1+z+z^2+\ldots\right)-\frac12\left(1+\frac z2+\frac{z^2}4+\ldots\right)=$$

$$=\frac1{2z}+\frac12+\frac{3z}4+\frac{7z^2}8+\ldots$$

Using that $\,\displaystyle{\frac1{1-w}=1+w+w^2+\ldots\;,\;\;\text{for}\;\;|w|<1}\,$ . I let you to write the above with a sum symbol, if you want.

For $\,A_2\,$ , again we get:

$$1<|z|<2\implies\frac1{|z|}<1\;,\;\;\frac{|z|}2<1 \;$$

so

$$\frac1{2z}-\frac1z\frac1{1-\frac1z}-\frac12\frac1{1-\frac z2}=\frac1{2z}-\frac1z\left(1+\frac1z+\frac1{z^2}+\ldots\right)+\frac12\left(1+\frac z2\frac{z^2}4+\ldots\right)=\ldots$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.